PERTUMBUHAN BIBIT BATANG BAWAH KARET DENGAN PEMBERIAN KOMPOS AMPAS TAHU DI MEDIA TAILING - ratih, ratih; Sopiana, Sopiana; Ratnawati Hermanto, Sarwendah (Politeknik Negeri Ketapang, 2024)
Tailings soil has limitations for being used as cultivation land, including the lack of organic material so that its texture does not easily hold water, nutrients and low pH. One thing that can be used as organic material is tofu dregs. This research aims to determine the effect of providing tofu dregs compost on the growth of rubber rootstock seedlings in tailings media. The research used a non-factorial Completely Randomized Design (CRD) with 5 treatment levels and 4 replications so that in total there were 20 experimental units and each experimental unit consisted of 3 samples so that the total number of seeds was 60 plants. Observation parameters included plant height (cm), stem diameter (mm), number of umbrellas (strands), primary root length (cm), root volume (mL), and analysis of tofu dregs compost and tailings soil. The data obtained were analyzed statistically using Analysis of Variance (ANOVA). If the treatment has a real effect, then a further Duncan Multiple Range Test (DMRT) 5% test is carried out. The results of variance analysis showed that the treatment of providing tofu dregs compost had a real influence on the variables of plant height, stem diameter, number of umbrellas, primary root length and root volume. Treatment with a dose of tofu dregs compost of 700 g/polybag is the best dose in increasing the growth of rubber rootstock seedlings.